PENGEMBANGAN MODUL MATA KULIAH ELEKTRONIKA DASAR II MATERI ROBOTIKA UNTUK MENINGKATKAN KEMANDIRIAN DAN PENGETAHUAN - Nehru, Nehru; Aldi, Ahmad; Basuki, Fibrika Rahmat (EduFisika: Jurnal Pendidikan Fisika, 2019)
This research aims to design basic electronics module II on robotics material and to know student perception. This research was research and development that uses the ADDIE model. The subject of this study was material experts, media experts, and 21 students. The instruments used were interview sheets, validation sheets, and questioner. Qualitative data analysis techniques are done descriptively and quantitative data is analyzed using descriptive statistics. The result was a printed module containing material about the basic robotics, controlling device, microcontroller, and an actuator. Modules were equipped with self-learning activities designing simple projects. Material expert validation results obtained a score of 84 with good categories and the validation result of media experts acquired score 109 with excellent categories. The student perception result of the module obtained a score of 1280 with good categories.